Improvised medicine providing care in extreme environments - Iserson, Kenneth V. (McGraw Hill Education, 2016)
"This second edition developed from the marked increase in published innovations applicable to medical improvisation. Clinicians throughout the world who dared to stretch their imaginations beyond the tight confines of medical conformity have produced marvelous innovations, generally stemming from the necessity to provide treatment in situations of acute or chronic shortages. Increasingly, clinicians have also recognized that the use of improvised techniques, equipment, and knowledge may be necessary not only in remote settings and in the developing world, but also in large medical centers and sophisticated emergency medical service (EMS) systems when confronted by medication and equipment shortages, localized crises, and major disasters. I am grateful for these clinicians' experiences and their support for Improvised Medicine, clearly an outlier from the staid teachings and guidelines of traditional practice."